2010
DOI: 10.1038/nphys1759
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature superconductivity in iron-based materials

Abstract: The surprising discovery of superconductivity in layered iron-based materials, with transition temperatures climbing as high as 55 K, has lead to thousands of publications on this subject over the past two years. While there is general consensus on the unconventional nature of the Cooper pairing state of these systems, several central questions remain - including the role of magnetism, the nature of chemical and structural tuning, and the resultant pairing symmetry - and the search for universal properties and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

44
1,542
6
14

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,519 publications
(1,606 citation statements)
references
References 199 publications
(256 reference statements)
44
1,542
6
14
Order By: Relevance
“…We find that the physical properties of the non-SC samples of (Li 1-x Fe x )OHFeSe are very similar to those of FeAsbased superconductors. [1][2][3][4]29 An emergent AFM SDW transition is observed at ~127 K in the absence of the well-known √5×√5 Fe vacancy ordered state associated with the AFM order in A y Fe 2-x Se 2 . In the optimal SC sample of (Li 1-x Fe x )OHFeSe with T c = 40 K, one dominant superstructure with a unique modulation wave vector q=1/2 (1,1,0) is observed by means of selected-area electron diffraction and high-resolution TEM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We find that the physical properties of the non-SC samples of (Li 1-x Fe x )OHFeSe are very similar to those of FeAsbased superconductors. [1][2][3][4]29 An emergent AFM SDW transition is observed at ~127 K in the absence of the well-known √5×√5 Fe vacancy ordered state associated with the AFM order in A y Fe 2-x Se 2 . In the optimal SC sample of (Li 1-x Fe x )OHFeSe with T c = 40 K, one dominant superstructure with a unique modulation wave vector q=1/2 (1,1,0) is observed by means of selected-area electron diffraction and high-resolution TEM.…”
mentioning
confidence: 99%
“…The SDW transition temperatures are much lower than that of the AFM transition of A y Fe 2-x Se 2 (its Neel temperature T N ~ 500 K). 5,13,[19][20][21]24,25 By contrast, such a SDW transition at 100-150 K has been commonly seen in the FeAs-based parent compounds of REFeAsO (RE = rare earth element), [1][2][3][4] whose structural skeleton containing FeAs layers is of the same P4/nmm symmetry as the present (Li 1-x Fe x )OHFeSe samples. The similar SDW transition indicates that its magnetic coupling strength is comparable to the FeAs-based counterparts, in consistent with the fact that their T c 's are similar.…”
mentioning
confidence: 99%
“…[1][2][3][4] The relationship between superconductivity and AFM fluctuations in recent-discovered iron-based superconductors has also been discussed. [5][6][7][8][9][10][11][12][13][14][15][16] Up to now, it has been reported that superconductivity appears around the AFM quantum critical point in the Ba122 system, indicative of the strong relationship between superconductivity and low-energy AFM fluctuations. 10,[12][13][14][15][16] On the other hand, superconductivity is linked not to the low-energy AFM fluctuations probed by NMR spectroscopy but to the local stripe spin correlation with Q stripe = (π, 0) (unfolded Brillouin zone) in LaFeAs(O 1−x F x ).…”
mentioning
confidence: 99%
“…From the viewpoint of theoretical and experimental evidences, [3][4][5] these superconductivities often emerge in the proximity of the ordering of spin/charge density wave instabilities, in contrast to that of conventional BCS superconductivity 6 .…”
Section: Introductionmentioning
confidence: 99%